2000
DOI: 10.1046/j.1469-8137.2000.00578.x
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic architecture of Monstera acuminata: evolutionary consequences of the hemiepiphytic growth form

Abstract: The hydraulic architecture of the secondary hemiepiphyte Monstera acuminata was examined in native plants from Los Tuxtlas, Veracruz, Mexico, to determine how it compared to better-known growth forms such as trees, shrubs, lianas and primary hemiepiphytes. Monstera acuminata starts its life cycle as a prostrate herb. As it ascends a tree or other vertical support, the stem becomes thicker, produces larger leaves, and may die back from the base upwards until only aerial feeding roots serve to connect the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 50 publications
4
30
0
Order By: Relevance
“…We found evidence that both vessel length and vessel diameter increased as the diameter of sampled stems increased. This is consistent with what has been reported in previous studies that found that vessel length ( Zimmermann and Jeje, 1981 ;Zimmermann and Potter, 1982 ;Ewers et al, 1990 ;Ewers and Fisher, 1989b ) and vessel diameter ( Zimmermann and Potter, 1982 ;Ewers andFisher, 1989b , Ewers et al, 1990 ;Sperry and Ikeda, 1997 ;López-Portillo et al, 2000 ;McCulloh et al, 2010 ) increased with plant age and/or stem size.…”
Section: Literature Citedsupporting
confidence: 93%
“…We found evidence that both vessel length and vessel diameter increased as the diameter of sampled stems increased. This is consistent with what has been reported in previous studies that found that vessel length ( Zimmermann and Jeje, 1981 ;Zimmermann and Potter, 1982 ;Ewers et al, 1990 ;Ewers and Fisher, 1989b ) and vessel diameter ( Zimmermann and Potter, 1982 ;Ewers andFisher, 1989b , Ewers et al, 1990 ;Sperry and Ikeda, 1997 ;López-Portillo et al, 2000 ;McCulloh et al, 2010 ) increased with plant age and/or stem size.…”
Section: Literature Citedsupporting
confidence: 93%
“…Both patterns are also cited for the aroid vine Monstera acuminata C. Koch (López‐Portillo et al . ). This stem structure could only be mechanically sustained if anchor roots are attached to the host trunk.…”
Section: Discussionmentioning
confidence: 97%
“…The internode measurements were subsequently extrapolated to the transverse section following López‐Portillo et al . ().…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…The same was shown by many studies at the whole-plant level, especially short-term ones involving pot-grown plants or seedlings. Thus, there seems to be consensus that like most of shallow-rooted agricultural crops, the hydraulic limitation is an important factor for tall and deep-rooted plant evolution as well (Lopez-Portillo et al 2000;Mencuccini 2003). Comparison of actual patterns of vessel branching of plants with models of vasculature proposed for plants show conflicting evolutionary pressures not only for water transport efficiency versus safety but also for mechanical strength (Niklas 1992;McCulloh and Sperry 2005).…”
Section: Discussionmentioning
confidence: 99%